Analysis Of The Effectiveness Of Using Tiktok Social Media As A Promotional Medium Using The EPIC Model At Alesha Shop Bara - Ammar Ibnu Arif; Ita Arfyanti; Bartolomius Harpad (Sebatik, 2026)
Social media promotional activities currently play a truly crucial role in significantly increasing brand awareness and public interest in Alesha Shop Bara. For this precise reason, conducting a comprehensive analysis of the effectiveness of utilizing this digital media is highly necessary for management to design and develop more optimal sales strategies in the future. In conducting this evaluation process, a highly applicable instrument or method is the EPIC Model, which was initially developed by the global market research firm, AC Nielsen. This particular evaluation model is specifically designed to comprehensively measure promotional effectiveness based on four main dimensions, which consist of empathy, persuasion, impact, and communication. To test and determine definitely whether the specific marketing strategy executed through the TikTok platform by Alesha Shop Bara has been completely effective, an objective measurement of the shop's TikTok performance itself is required. Based on the final results of the data analysis, it can be concluded that Alesha Shop Bara's TikTok is proven to be a highly effective promotional medium. This positive result is strongly evident from the excellent scores achieved in the empathy, persuasion, impact, and communication dimensions. Overall, the average score of the EPIC rate obtained is 4.42, with the empathy dimension successfully achieving the highest score compared to the other dimensions, reaching 4.49.